Interaction of Pseudomonas Bacteriophage 2 with the Slime Polysaccharide and Lipopolysaccharide of Pseudomonas aeruginosa Strain BI - Bartell, Pasquale F. (1971)
Purified slime polysaccharide B and lipopolysaccharide of Pseudomonas aeruginosa strain BI were shown to possess receptor-like properties in inactivating Pseudomonas phage 2, whereas lipoprotein and glycopeptide fractions were devoid of activity. On a weight basis, slime polysaccharide B was more effective than lipopolysaccharide in inactivating phage. The specificity of the reaction with slime polysaccharide B was indicated by the fact that slime polysaccharide A of P. aeruginosa strain EI failed to inactivate phage 2. Electron micrographs showed phage 2 in typical, tail-first position of attachment on intact cells of strain BI, slime polysaccharide B, and lipopolysaccharide. Tail fibers were discernible during phage attachment.